2019
DOI: 10.1016/j.physletb.2019.134893
|View full text |Cite
|
Sign up to set email alerts
|

The onset of ΛΛ hypernuclear binding

Abstract: Binding energies of light, A ≤ 6, ΛΛ hypernuclei are calculated using the stochastic variational method in a pionless effective field theory (/ πEFT) approach at leading order with the purpose of assessing critically the onset of binding in the strangeness S = −2 hadronic sector. The / πEFT input in this sector consists of (i) a ΛΛ contact term constrained by the ΛΛ scattering length aΛΛ, using a range of values compatible with ΛΛ correlations observed in relativistic heavy ion collisions, and (ii) a ΛΛN conta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 56 publications
6
39
0
Order By: Relevance
“…(18) onto the basis Eq. (19), one obtains the flow equation in form of an integro-differential equation…”
Section: Srg Evolution For Chiral Nn and Yn Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…(18) onto the basis Eq. (19), one obtains the flow equation in form of an integro-differential equation…”
Section: Srg Evolution For Chiral Nn and Yn Interactionsmentioning
confidence: 99%
“…For local interactions, configuration space methods, e.g. hyperspherical harmonics, Green's function Monte Carlo, expansion in Gaussians or stochastic variational method (SVM), have been successfully used to predict properties of light hypernuclei [16][17][18][19][20]. For very light systems, that goal can be likewise achieved by solving the Faddeevor Yakubovsky equations in momentum space [15,[21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Two bound states are found B Ξ = 13.5 MeV with (T, J π ) = (1/2, 3/2 + ) and B Ξ = 0.012 MeV with (T, J π ) = (1/2, 1/2 + ) with respect to the d + Ξ threshold. In addition, one bound state is found to be 1 33. MeV with (T, J π ) = (3/2, 1/2 + ) with respect to the D * + N threshold.…”
mentioning
confidence: 95%
“…14, using local central Yukawatype Malfliet-Tjon interactions, concluded that the ΛΛnn system is unbound by a large margin. A recent calculation using the stochastic variational method in a pionless effective field theory approach 15 come to the identical conclusion. It is important to notice that in order to create a ΛΛnn bound state the four particles must coincide simultaneously since the system does not contain two-or three-body subsystem bound states, so that the probability of the event occurring is rather small.…”
Section: Introductionmentioning
confidence: 64%
“…Pionless effective field theory and the 3 ΛΛ n and 4 ΛΛ n systems Recently, Contessi et al 15 used a stochastic variational method to perform the first comprehensive pionless effective field theory study of ΛΛ hypernuclei with A ≤ 6. In addition to the interaction terms involved in the description of single-Λ hypernuclei, a two-body ΛΛ contact term constrained to the ΛΛ scattering length a ΛΛ was considered.…”
Section: 3mentioning
confidence: 99%